The effectiveness of the promotional tools used by Pusat Zakat Negeri Sembilan in enhancing customer awareness / Nor Syuhada Ali - Ali, Nor Syuhada (Faculty of Business and Management, 2007)
The messenger of Allah S.W.T (peace is upon him) was ordered to fight the people until they made the syahada, established prayer and paid zakat. Therefore, Pusat Zakat Negeri Sembilan want to make sure that Muslim pay the zakat and fulfill all of the others pillar of Islam correctly and sincerely for Allah S.W.T sake so that our religion will be strong and Allah S.W.T will be pleased with us. In order to increase zakat collection, promotional effort is important and to be stressed in order to achieve the amount of zakat collection targeted. This is challenges found by PZNS to maintain the zakat collection that has been set every year.